Effects of Passi/Zora /oetida Linn. (Passifloraceae) on Genital Tract, Serum Estradiol, Pituitary Gonadotropin and Prolactin Level in Female Adult and Immature Ovariectomized Rats: Phytochemical Effects of Passiflora foetida on Rats - Michel, Bleu Gome; Koffi, Kouakou; Alassane, Toure; Flavien, Traore (Biological Sciences - PJSIR, 2012)